The presence of kiwifruit columella affects the aroma profiles of fresh and thermally treated kiwifruit juice. (1st August 2022) - Xu, Sujuan; Zhan, Ping; Tian, Honglei; Wang, Peng
Abstract: The aroma-active compounds in the whole fruit, pulp, and columella of fresh and thermally treated kiwifruit from three varieties (CX), (HW), and (XX) were analyzed. Major aroma-active C6 alcohols and aldehydes were abundant in the pulp, while key esters were predominant in the columella. Quantitative descriptive analysis (QDA) indicated that the heating of pulp caused large changes in the fruity and sweet notes, while the intensities of grassy, pungent, and cooked cabbage notes in thermally treated whole kiwifruit (TW) were considerably stronger than thermally treated pulp (TP). Based on GC-MS/O and OAV, 17 odor-active compounds were identified. TP had substantial reductions in key alcohols and aldehydes, and the presence of columella attenuated the heat losses in characteristic esters. Decanal, (E)-2-decenal, 1-octen-3-one, and dimethyl sulfide, formed during heating, were positively correlated with the cooked cabbage odor by partial least-squares regression (PLSR). Hierarchical cluster analysis (HCA) revealed that aroma profiles of TP in CX and HW were similar to fresh samples, suggesting that the columella indeed affected the aroma profile during thermal treatment, especially for CX and HW. Altogether, these results could offer recommendations for kiwifruit juice processing to improve the aroma quality of juice products by changing the content of columella. Highlights: The volatile compositions between the pulp and columella of three kiwifruit varieties were compared. The effects of the presence of columella on the sensory profile of thermally treated kiwifruit juices were investigated. The removal of columella promoted the aroma profile of thermally treated kiwifruit juice to be closer to that of fresh juice.